Pine Shoot Beetle, Tomicus piniperda (Linnaeus) (Insecta: Coleoptera: Curculionidae: Scolytinae) - Michael C. Thomas; Wayne N. Dixon; Thomas R. Fasulo (EDIS, 2010)
Revised! EENY-321, a 6-page illustrated fact sheet by Michael C. Thomas, Wayne N. Dixon, and Thomas R. Fasulo, is part of the Featured Creatures collection. It describes this serious pest of pines in Europe that is considered a potential threat to some of the pine species cultivated in Florida — distribution, identification, biology, economic importance, survey, and management. Includes references. Published by the UF Department of Entomology and Nematology, September 2010.